From Exchange to Inter-knowledge: Ethnography and the Invisible Facts of Political Work - Quirós, Julieta (2018)
Based on an ethnographically situated study of recent electoral processes in Argentina, this study contributes to the understanding of politics and political activities of which the protagonists- politicians and political activists or operators- refer to as the territorio or local level. Drawing on ethnographic observation from different contexts- both rural and urban areas-, the case is made for the need to rescue analytically the concept of agency and the importance of personal relations that both common sense and the scholarly literature often consider politically “weak”. An alternative approach is put forward for the future research agenda which centres on inter-knowledge in the use of technology used within the political work of political leaders, candidates and activists in the process of creating relations of political representation. In addition, the importance of understanding different scales of the local, the State and government are also analysed.